2009
DOI: 10.1016/j.juro.2008.10.067
|View full text |Cite
|
Sign up to set email alerts
|

New Histopathological Experimental Model for Benign Prostatic Hyperplasia: Stromal Hyperplasia in Rats

Abstract: We have established a new experimental stromal hyperplasia model corresponding to clinical benign prostatic hyperplasia in terms of the composition of stromal components and functional differentiation of the prostate. Furthermore, the localization and time course of growth factor expression were also similar to those in men with benign prostatic hyperplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…Experimental model rats for BPH with stromal hyperplasia were prepared as reported previously (Mori et al, 2009). Implanted UGS and normal host prostate in stromal hyperplasia BPH model rats were dissected 3 weeks after implantation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental model rats for BPH with stromal hyperplasia were prepared as reported previously (Mori et al, 2009). Implanted UGS and normal host prostate in stromal hyperplasia BPH model rats were dissected 3 weeks after implantation.…”
Section: Methodsmentioning
confidence: 99%
“…The major component of clinical BPH specimens is stromal extracellular matrix, which is organized by smooth muscle, fibrous tissue element, and collagen (Shapiro et al, 1992); however, this feature is histologically different from the testosterone-induced rodent BPH model (Ishigooka et al, 1996), and this animal BPH model is not adequate to elucidate the pathological mechanisms of stromal hyperplasia. Mori et al (2009) recently established a new experimental rodent model characterized by stromal hyperplasia. Urogenital sinuses implanted into the ventral prostate, "implanted UGS," contain a much higher ratio of stroma than the agematched ventral prostate and the testosterone-induced BPH model and are similar to those in men with BPH.…”
Section: Introductionmentioning
confidence: 99%
“…Urogenital sinus implanted into the ventral prostate, 'implanted urogenital sinus (UGS),' contains a much higher ratio of stromal components than the age-matched ventral prostate, and are similar to those in men with BPH. 25) We have shown that K Ca 3.1, which encodes intermediate-conductance Ca 2+ -activated K + (IK Ca ) channel is up-regulated in prostatic stromal cells of stromal hyperplasia BPH model and in those of prostatic tissues from BPH patients. 26) Pharmacological IK Ca channel blockade has shown significant suppression of the implanted UGS proliferation index in stromal compartment but not in epithelial one.…”
Section: +mentioning
confidence: 99%
“…25) Implanted urogenital sinuses (UGSs) and normal host prostates in stromal hyperplasia BPH model rats were dissected 4 weeks after implantation. All experiments were carried out in accordance with the guiding principles for the care and use of laboratory animals (the Science and International Affairs Bureau of the Ministry of Education, Culture, Sports, Science and Technology of Japan) and also with the approval of the ethics committees of Nagoya City University and Taiho Pharmaceutical Co., Ltd. Total RNAs from human normal prostates were purchased from BD Biosciences (San Jose, CA, U.S.A.) and BioChain (Hayward, CA, U.S.A.) (21-50 years old, three distinct Lot No.…”
Section: Rna Extraction Reverse Transcription (Rt)-pcr Andmentioning
confidence: 99%
See 1 more Smart Citation